A Fluoroquinolone Resistance Associated Mutation in gyrA Affects DNA Supercoiling in Campylobacter jejuni - Han, Jing; Wang, Yang; Sahin, Orhan; Shen, Zhangqi; Guo, Baoqing; Shen, Jianzhong; Zhang, Qijing (Frontiers in Cellular and Infection Microbiology, 2012)
The prevalence of fluoroquinolone (FQ)-resistant Campylobacter has become a concern for public health. To facilitate the control of FQ-resistant Campylobacter, it is necessary to understand the impact of FQ resistance on the fitness of Campylobacter in its natural hosts as understanding fitness will help to determine and predict the persistence of FQ-resistant Campylobacter. Previously it was shown that acquisition of resistance to FQ antimicrobials enhanced the in vivo fitness of FQ-resistant Campylobacter. In this study, we confirmed the role of the Thr-86-Ile mutation in GyrA in modulating Campylobacter fitness by reverting the mutation to the wild-type allele, which resulted in the loss of the fitness advantage. Additionally, we determined if the resistance-conferring GyrA mutations alter the enzymatic function of the DNA gyrase. Recombinant wild-type gyrase and mutant gyrases with three different types of mutations (Thr-86-Ile, Thr-86-Lys, and Asp-90-Asn), which are associated with FQ resistance in Campylobacter, were generated in E. coli and compared for their supercoiling activities using an in vitro assay. The mutant gyrase with the Thr-86-Ile change showed a greatly reduced supercoiling activity compared with the wild-type gyrase, while other mutant gyrases did not show an altered supercoiling. Furthermore, we measured DNA supercoiling within Campylobacter cells using a reporter plasmid. Consistent with the results from the in vitro supercoiling assay, the FQ-resistant mutant carrying the Thr-86-Ile change in GyrA showed much less DNA supercoiling than the wild-type strain and the mutant strains carrying other mutations. Together, these results indicate that the Thr-86-Ile mutation, which is predominant in clinical FQ-resistant Campylobacter, modulates DNA supercoiling homeostasis in FQ-resistant Campylobacter.